Examining the Nature of Theory–Practice Relationships in Initial Teacher Education: A Canadian Case Study - Goodnough, Karen; Falkenberg, Thomas; MacDonald, Ron (Canadian Journal of Education/Revue canadienne de l’éducation, 2016)
In this case study, the authors examined how theory practice relationships were conceptualized and enacted in a new teacher preparation program. As well, the issues and tensions associated with theory–practice dynamics were explored. More specifically, the authors explored two questions: (a) What is the nature of theory–practice relationships in a new teacher preparation program? (b) What tensions will arise as theory–practice relationships are manifested in this new teacher preparation program? Through the analysis of a number of qualitative data sets, insights are shared about program design, practices, and pedagogy, as well as the perspectives of teacher educators and teacher candidates on the nature of theory–practice relationships in their teacher preparation programs. Implications for teacher educators and teacher preparation are discussed.